2009
DOI: 10.1515/cclm.2009.261
|View full text |Cite
|
Sign up to set email alerts
|

Level of selenoprotein transcripts in peripheral leukocytes of patients with bladder cancer and healthy individuals

Abstract: Background: Low concentrations of selenium (Se) in humans have been associated with risk of cancer. Selenoprotein mRNAs can potentially be regulated by Se status. Methods: Se status, GPx1 Pro198Leu and Sep15 1125G/A genetic polymorphism and human (h)GPx1, hGPx3, hSep15 and hSeP1 transcript levels in peripheral leukocytes of 33 males with bladder cancer and 47 healthy male controls were analysed. Results: All the subjects expressed detectable selenoprotein mRNA concentrations in leukocytes. Significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
2
19
1
7
Order By: Relevance
“…Of note, the T allele, associated with an increased risk of breast cancer in African women [16], colorectal cancer in Asian men [23], and lung cancer in Caucasians with low Se levels [11], occurs generally more often in African-Americans (31 vs. 7 %) [16]. Therefore, similar to other studies [30,40,41], our results can be impacted by the overall lower presence of the T allele in Caucasians (2-2.4 % TT homozygotes in our data sets).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Of note, the T allele, associated with an increased risk of breast cancer in African women [16], colorectal cancer in Asian men [23], and lung cancer in Caucasians with low Se levels [11], occurs generally more often in African-Americans (31 vs. 7 %) [16]. Therefore, similar to other studies [30,40,41], our results can be impacted by the overall lower presence of the T allele in Caucasians (2-2.4 % TT homozygotes in our data sets).…”
Section: Discussionsupporting
confidence: 63%
“…In animal models, changes in the Sep15 structure promoted the experimental carcinogenesis in the mammary gland in mice [21,22]. However, as shown in Table 3, the described link between Sep15 Hu [16] Breast 60 African-American (USA) Increased cancer risk in CG/CG homozygotes Hu [16] Head and neck 33 African-American (USA) Decreased risk in CG/TA heterozygotes Hu [16] Head and neck 94 Caucasian (USA) No association Hu [16] Chronic myelogenous leukemia No association for SEP15 alone; two-loci interaction between SEPP1 and SEP15 3′-UTR polymorphisms and cancer susceptibility is not obvious [11,16,[23][24][25][26][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, emerging studies have been done to evaluate the association between GPx-1 Pro198Leu polymorphism and risks for diVerent types of tumor in diverse populations, such as breast cancer (Ravn-Haren et al 2006;Cox et al 2004;Ahn et al 2005;Hu and Diamond 2003;Knight et al 2004;Cebrian et al 2006), lung cancer (Rosenberger et al 2008;Yang et al 2004;Ratnasinghe et al 2000;RaaschouNielsen et al 2007;Skuladottir et al 2005;Lee et al 2006), bladder cancer (Ichimura et al 2004;Paz-y-Mino et al 2010;Reszka et al 2009;Goerlitz et al 2011), prostate cancer (Choi et al 2007;Arsova-SaraWnovska et al 2009;Steinbrecher et al 2010), colorectal cancer Hansen et al 2005Hansen et al , 2009 and other cancers (Rajaraman et al 2008;Bhatti et al 2009;Wang et al 2008;Hu et al 2004;Ezzikouri et al 2010;Lightfoot et al 2006;Wu et al 2010;Tang et al 2010;Vogel et al 2004;He et al 2011). However, the results from those studies remain debatable rather than conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a number of studies failed to find such relationships, or only found it in specific subgroups, such as smokers [11][12][13][14][15] .…”
Section: Observational Evidencementioning
confidence: 99%